Implementation of the project based learning model in improving chemistry achievement for class XI MIPA 4 students at SMAN 1 north halmahera - Grace Sylvia Baud (12 Waiheru, 2023)
This research aims to be an effort to improve students’ achievement in chemistry subjects, especially class XI MIPA 4 at SMAN 1 North Halmahera, especially in acid-base material. The type of research used is classroom action research (PTK), with a Project-Based Learning (PjBL) model in the form of a practicum. The results of the first cycle of research showed that 34% of students were able to achieve the KKM, in the second cycle after follow-up in the form of practice questions and practice, 77% of students were able to achieve the KKM, in the third cycle they continued with practicum and were given the task of making a report on the results of the practicum, 89% were obtained. students who reach the KKM. Based on the research results, it is highly recommended that the PjBL learning model be used in chemistry learning so that students can understand the concept and application of acid-base material in everyday life.